Corruption Arrest Hand Operation based on Wiretapping Process Conducted by The Corruption Eradication Commission from The Perspective of Islamic Criminal Law - Muhammad Arri Widiawan; M. Junaidi (Universitas Muhammadiyah Surakarta, 2024)
The Corruption Eradication Commission is an independent institution responsible for handling cases related to corruption, the Corruption Eradication Commission itself has the freedom to conduct investigations to bring into the realm of law against a person or a corporation suspected of being a perpetrator of corruption. Within the Corruption Eradication Commission itself, there is a Trident that it uses in enforcing the law against corruption. One of the Trident, there is the freedom given to the Corruption Eradication Commission to carry out wiretapping actions to prevent a crime of corruption which can then be claimed as one of the most successful efforts in stopping the crime of corruption. This then raises unrest and very brutal questions about the freedom possessed by the Corruption Eradication Commission to access personal data or personal property belonging to a person on the grounds of preventing corruption. This is a violation of a person's privacy data, and can be said to violate human rights which are deliberately protected by law. Islam then comes to provide some answers to the actions taken by the Corruption Eradication Commission, Islam does not only look from the angle of the aggrieved or from the narrow angle of the solution offered. However, this is part of Fiqh, which in a broad sense has many different meanings and understandings. This research will provide an overview of how Islamic law and the criminal context regarding wiretapping actions taken by the Corruption Eradication Commission to prevent corruption. This research uses Normative research methods and descriptively will provide a broad and concise description and provide examples of examples or actions that can be a way out.